High-throughput method development for in-situ quantification of aquatic phototrophic biofilms. Issue 5 (28th May 2022) - Papadatou, Maria; Knight, Mollie; Salta, Maria
Abstract: In the maritime field where biofouling has both economic and environmental impacts, in situ quantification methods of biofilm development are of outstanding importance. Indeed, it is challenging to temporally monitor biofilm formation due to the complexity of the marine ecosystem, common inaccessibility of sampling location and lack of standardized techniques. Here, an artificial polymeric surface was tested in situ and in vitro against natural phototrophic biofilms and monoculture biofilms using plate reader fluorescence. The suitability of the developed method was verified using fluorescence microscopy coupled with image analysis - a common quantification technique - demonstrating a strong correlation between the tested methods. The results indicated the efficiency of inherent chlorophyll fluorescence in quantifying undisturbed phototrophic biofilms in field and laboratory conditions using microplate reader. This work demonstrated that the suggested approach is promising for biofilm high-throughput testing, and therefore has the potential to be used in several research and industrial sectors for monitoring phototrophic biofilm development.